The Crosstalk of the Salicylic Acid and Jasmonic Acid Signaling Pathways Contributed to Different Resistance to Phytoplasma Infection Between the Two Genotypes in Chinese Jujube - Wang, Lixin; Liu, Shiyan; Gao, Mengjiao; Wang, Lihu; Wang, Linxia; Wang, Yunjie; Dai, Li; Zhao, Jin; Liu, Mengjun; Liu, Zhiguo (Frontiers in Microbiology, 2022)
Jujube witches’ broom disease (JWB), one of the most serious phytoplasma diseases, usually results in the destruction of Chinese jujube (Ziziphus jujuba Mill.). Although most jujube cultivars are sensitive to JWB, we found a few genotypes that are highly resistant to JWB. However, the molecular mechanism of phytoplasma resistance has seldom been studied. Here, we used Chinese jujube ‘T13’, which has strong resistance to JWB, and a typical susceptible cultivar, ‘Pozao’ (‘PZ’), as materials to perform comparative transcriptome, hormone and regulation analyses. After phytoplasma infection the DEGs were detected at all three growth phases (S1, S2 and S3) in ‘PZ’, but DEGs were detected only at the first growth phase in ‘T13’. Meanwhile, no phytoplasma was detected, and JWB symptoms were not observed at the last two growth phases (S2 and S3) in ‘T13’. Protein-protein interaction analysis also showed that the key genes were mainly involved in hormone and reactive oxygen species (ROS) signalling. In addition, during the recovered growth phase in ‘T13’ from S1 to S2, the level of hydrogen peroxide (H2O2) was significantly increased and then decreased from S2 to S3. Moreover, jasmonate acid (JA) was significantly accumulated in ‘PZ’ diseased plants, especially at the S2 phase and at the S2 phase in ‘T13’, while the content of salicylic acid (SA) decreased significantly at the S2 phase of ‘T13’ compared to that in ‘PZ’. The changes in H2O2 and JA or SA were consistent with the changes in their key synthesis genes in the transcriptome data. Finally, exogenous application of an SA inhibitor (1-aminobenzotriazole) rescued JWB symptoms, while the contents of both JA and MeJA increased after 1-aminobenzotriazole treatment compared to the control, demonstrating that exogenous application of an SA inhibitor rescued the symptoms of jujube after phytoplasma infection by decreasing the contents of SA and increasing the contents of JA and MeJA. Collectively, our study provides a new perspective on the transcriptional changes of Chinese jujube in response to JWB disease and novel insights that the crosstalk of JA and SA signalling communicated together to contribute to ‘T13’ JWB resistance.